2009
DOI: 10.4070/kcj.2009.39.11.467
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trend in the Incidence of Acute Myocardial Infarction in Korea: 1997-2007

Abstract: Background and ObjectivesInformation about disease incidence is indispensable for the active prevention and control of acute myocardial infarction (AMI). The purpose of this study was to provide basic information for the establishment of policy related to AMI by examining the long-term trends in incidence of AMI.Subjects and MethodsThis study identified the trend in disease incidence during between 1997 and 2007 using the Korean National Health Insurance Database that includes AMI {the 10th International Class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 26 publications
(32 reference statements)
4
62
0
Order By: Relevance
“…4-8, 11 The same trend in reduced in-hospital mortality of AMI was also noted in Korea and Taiwan between late1990 s and 2000 s ( Table 2). 12, 13 Similarly, in Japan, we also previously reported that in-hospital mortality of AMI markedly decreased between 1980 and 2008. 19 of the improvement in the critical care of AMI, including shorter elapsed time from onset to admission and increasing performance rate of primary PCI, and the increasing prevalence of heart failure with Killip class ≥2 on admission, remain to be fully elucidated.…”
Section: Trends In the In-hospital Mortality Of Amimentioning
confidence: 99%
See 2 more Smart Citations
“…4-8, 11 The same trend in reduced in-hospital mortality of AMI was also noted in Korea and Taiwan between late1990 s and 2000 s ( Table 2). 12, 13 Similarly, in Japan, we also previously reported that in-hospital mortality of AMI markedly decreased between 1980 and 2008. 19 of the improvement in the critical care of AMI, including shorter elapsed time from onset to admission and increasing performance rate of primary PCI, and the increasing prevalence of heart failure with Killip class ≥2 on admission, remain to be fully elucidated.…”
Section: Trends In the In-hospital Mortality Of Amimentioning
confidence: 99%
“…9-11 In contrast, in Asian countries, including Japan, Taiwan and Korea, AMI has become more common because of prolonged life expectancy, rapid socioeconomic advances, and westernization of life style and diet. 12, 13 In Japan, there have been a few registry studies of AMI and most of them included a relatively small number of patients and/or a relatively short study period. 14- 17 In order to elucidate the accurate trend of AMI in Japan, we have been conducting the Miyagi AMI Registry Study for 37 Age-Specific Trends in AMI in Japan (STEMI) vs. non-STEMI] was unavailable for most of the study period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate interventions may decrease the disability and death rates due to acute myocardial infarction (AMI) [14]. Several countries have added AMI to the list of targets to be monitored and assessed at the national level [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several countries have added AMI to the list of targets to be monitored and assessed at the national level [14]. In this monitoring, hospital performance has been compared based on quality of care measures [5–9].…”
Section: Introductionmentioning
confidence: 99%